HVOR BOR DE VILDE? Erindringer om identitet og politik i Amazonas - Hvalkof, Søren (Tidsskriftet Antropologi, 1997)
Søren Hvalkof: Where are the Savages? Memories of Identity and Politics in the Amazon The author’s personal experience with a conventional study tour to the Peruvian Andes that metamorphosed into an ethnographic joumey of the Amazon, highlights the central importance of the ethnographic field work as anthropology’s phenomenological soul. The case of the Asheninka of the Peruvian Amazon is used to show why the ethnographic description is crucial to the realization of the political potentials inherent in non-Westem societies. Using classificatory models of ethnic and social identity developed by Dr. Niels Fock and rethinking them in the context of power, the epistemological contrast between the developmentalist and essentialist monolith of Western thinking and the indigenous, nonessentialist, multicentric and particularistic universe is demonstrated. The recent political success of the latter is related to the potentials released through the growing process of globalization. An anecdote from the field epitomizes the choices made by the Asheninka.